The Dickens boy : a novel - Keneally, Thomas (Atria Books, an imprint of Simon & Schuster, Inc., 2022)
Edward Dickens, the tenth child of author Charles Dickens, has consistently let down his parents. Unable to apply himself at school and adrift in life, the teenaged boy is sent to Australia in the hopes that he can make something of himself - or at least fall out of the public eye. Determined to prove to his parents and more importantly, himself, that he can succeed in this vast and unfamiliar wilderness, Edward works hard at his new life amidst various livestock, bushrangers, shifty stock agents, and frontier battles.